Analysis Of Financial Performance In An Islamic Perspective In PT. Garuda Indonesia (Persero) Tbk - Siregar, Rajab; Nurlaila, Nurlaila; Syahbudi, Muhammad (Yayasan Cita Cendekiawan Al Khwarizmi, 2022)
This study aims to analyze the solvency ratio and activity as an assessment tool to measure financial performance at PT. Garuda Indonesia in an Islamic perspective. This study uses a qualitative descriptive approach, while the data studied are in the form of the financial statements of PT. Garuda Indonesia from 2017 to 2020. From the results of the calculation of the average solvency ratio as measured by the debt-to-asset ratio and the debt-to-equity ratio from 2017 to 2020, the activity ratio as measured by the total asset turnover ratio and the ratio Fixed asset turnover in 2017 to 2020 was not good. PT. Garuda Indonesia in the Islamic perspective is in accordance with the accounting contained in the Qur'an Al-Baqarah verse 282, namely the principle of responsibility as it cannot be separated from the responsibility of someone assigned to make financial reports in accordance with transactions that occur during muamalah. The principle of justice PT. Garuda Indonesia has implemented justice, namely recording all transactions that have occurred as they should be from assets, liabilities, capital, revenues and costs incurred by the company, while the principle of truth is that transactions occur in the ratio of liquidity, activity, solvency and profitability, both transactions of assets, liabilities, capital, income and expenses of each item are appropriate and included in the financial statements of PT. Garuda Indonesia.